Role of airway epithelial cell miRNAs in asthma - Boateng, Eistine; Kovacevic, Draginja; Oldenburg, Vladimira; Rådinger, Madeleine; Krauss-Etschmann, Susanne (Frontiers in Allergy, 2022)
The airway epithelial cells and overlying layer of mucus are the first point of contact for particles entering the lung. The severity of environmental contributions to pulmonary disease initiation, progression, and exacerbation is largely determined by engagement with the airway epithelium. Despite the cellular cross-talk and cargo exchange in the microenvironment, epithelial cells produce miRNAs associated with the regulation of airway features in asthma. In line with this, there is evidence indicating miRNA alterations related to their multifunctional regulation of asthma features in the conducting airways. In this review, we discuss the cellular components and functions of the airway epithelium in asthma, miRNAs derived from epithelial cells in disease pathogenesis, and the cellular exchange of miRNA-bearing cargo in the airways.